The anatomical relationship between the mandibular first molar roots and the mandibular canal based on breed size and skull type - Greene, Erica; Rendahl, Aaron; Goldschmidt, Stephanie (Frontiers in Veterinary Science, 2022)
The first molar is the largest tooth in the dog mandible with roots often extending to the level of the mandibular canal (MC). The anatomical relationship between the roots and MC is variable and the normal relationship between those structures in a diverse population of dogs has not been established. Lingual location of the roots relative to the MC poses a risk for iatrogenic trauma during dentoalveolar surgery, and it is unknown if certain skull conformations are predisposed to this relationship. The aim of this study was to identify associations between patient weight and skull type with molar tooth root location. Computed Tomography (CT) scans performed for reasons unrelated to the study were retrospectively analyzed. Subjects were sorted into one of 12 groups (n=16 per group) based on skull type (brachycephalic, mesaticephalic, dolichocephalic) and weight (extra small: if ≤6.8 kg, small: if >6.8 kg and- ≤13.6 kg, medium: if >13.6 kg and- ≤25 kg, or large if >25 kg and- ≤ 38.6 kg). The mandibular first molar roots were categorized as lingual, buccal, or dorsal relative to the MC. Lingual root location was diagnosed in 50.0% of all roots evaluated, and 64.2% of all dogs assessed had at least one root in the lingual position. Size was shown to be protective, with lingual root location being significantly less likely as size increased. The exception to this was in large brachycephalic patients, which had rates of lingual roots similar to smaller dogs. Buccal roots were rarest, diagnosed in only 9.7% of all roots, and were most common in brachycephalic patients, which had 83.8% of all buccal roots. Additional caution should be employed when removing alveolar bone during surgical extraction in dogs ≤ 13.6 kg and in large brachycephalic patients (boxers) to avoid iatrogenic trauma to the neurovascular bundle.